Ewnik
Rozwiązane

Rozwiąż równanie
(x+3)(2x-7)+8=(x-4)(2x+2)

musi wyjść wynik. 1



Odpowiedź :

Rozwiązanie:

(x + 3)(2x - 7) + 8 = (x - 4)(2x + 2)

x(2x - 7) + 3(2x - 7) + 8 = (x - 4)(2x + 2)

2x² - 7x + 3(2x - 7) + 8 = (x - 4)(2x + 2)

2x² - 7x + 6x - 21 + 8 = (x - 4)(2x + 2)

2x² - x - 21 + 8 = (x - 4)(2x + 2)

2x² - x - 13 = (x - 4)(2x + 2)

2x² - x - 13 = x(2x + 2) - 4(2x + 2)

2x² - x - 13 = 2x² + 2x - 4(2x + 2)

2x² - x - 13 = 2x² + 2x - 8x - 8

2x² - x - 13 = 2x² - 6x - 8

-x + 6x = -8 + 13

5x = 5      / : 5

x = 1

Mam nadzieję, że pomogłam ;)

Pozdrawiam